Phonological Construction of Indonesian Blends - Karjo, Clara Herlina (Linguistik Indonesia, 2024)
Blends are formed by joining two clipped words into one. For example, in English, ‘breakfast’ and ‘lunch’ are joined to become ‘brunch’. While studies of blends usually focus on the morphological aspect, this study aims at describing the phonological aspects of blend formation, particularly the syllable formation of Indonesian blends. Moreover, the phonological constraints for blend formation are also investigated. The data were obtained from observing blending words used in daily conversations, as well as in media such as television and online news. To gather the data, the researcher asked each of her 20 students to find five samples of Indonesian blends. As a result, as many as 100 Indonesian blends were found. The data were then categorized based on their syllable structures and the phonological constraints for blend formation were analyzed using optimality theory. The results showed that blending words can be categorized into six types, which are (CVC+CVC), (CV+CVC), (CV+CVC), (V+CVC), (CV+CV), and (VC+CVC). For example, the second type (CV + CVC) ‘mager’ is formed from the first part of the first source word and the first part of the second source word as in ‘malas’ and ‘gerak’. Moreover, there are some possible constraints that make a new blend acceptable or unacceptable in Indonesian, such as the recognizability of blend from its source words and the semantic similarity of the blend with the already existing word. For example, the word ‘mantul’ is acceptable blend of mantap + betul, since ‘mantul’ already exists but it has different meaning. The results of this study imply that forming new words by blending the already existed words is still possible, but their acceptance or usage depend on the users’ familiarity with phonological knowledge.